Assessing the clinical impact and resource use of a 30-minute chlamydia and gonorrhoea point-of-care test at three sexual health services. (December 2021) - Huntington, Susie; Weston, Georgie; Adams, Elisabeth
Objectives: To assess clinical metrics and resource use of a 30-minute point-of-care test (POCT) for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) compared to laboratory-based testing. Methods: Three English sexual health services (SHSs) were recruited as part of a study. Existing processes for CT/NG testing and treatment were assessed, and adaptions to incorporate the CT/NG POCT were developed during semi-structured interviews. Staff time and consumables data were collected by clinic staff prior to and following introduction of the POCT. Results: SHSs selected patient groups for whom the CT/NG POCT would be used. Testing and treatment process data were collected for 225 patients (n = 118 POC; n = 107 standard). The percentage of patients receiving unnecessary CT treatment was 5% (5/95) and 13% (12/93) for POC and standard care respectively. The average CT/NG pathway cost varied and was on average £61.55 for POC and £50.88 for standard care. For the two SHSs where the POCT was used during a patient's visit, for standard and POC respectively, the average time to CT treatment was 10.0 and 0.0 days and to NG treatment, 0.3 and 0.0 days. Conclusion: Use of a 30-minute POCT at three SHSs yielded clinical benefits by reducing time to treatment and unnecessary CT treatment.